Muhammadiyah dan Problema Hubungan Agama-Budaya - Biyanto, Biyanto (Program Pascasarjana UIN Sunan Ampel Surabaya, 2010)
This article deals with Muhammadiyahâs view of the inter-connection between religion and culture. Religion is a divine product while culture is a human invention. How these two different domains are inter-related will be a kind of formidable task to expose. To do this, the paper will discuss first the possible relation between Muhammadiyah and Salafiyah as far as theology is concerned. Many have contended that Muhammadiyah is an extension of this rabian theology. The paper will try to trace if there is any such theological relation between the two by appealing to some basic concepts that both Muhamadiyah and Salafiyah hold such as the concept of puritanism; that the Qurâan and the prophetic traditions are the sole sources for both religion and culture. But we also try to explore the unique aspect of each movement of which the other does not share. Thus, Muhammadiyahâunlike Salafiyahâhas a good deal of awareness in culture and even adopts the âcultural approachâ in propagating Islam. As a religious organization whose task lies mainly in calling people into Islam, Muhammadiyah has advocated what is commonly known as the âdakwah culturalâ; a cultural approach in dakwah. For this purpose, Muhammadiyah has designed a guidebook on how âdakwah kulturalâ is carried out, its steps, and strategies. In writing his paper, we hope to shed a better light on the objective nature of Muhammadiyah and its view concerning religion and culture.